A Comprehensive Survey on Stake Cloud Computing - et. al., Ms. R. Aishwarya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years the development of devices in both smart and intelligent are unlimited. Because of this, many new applications are trending such as Smart house, Smart cities, Virtual reality, Augmented reality, Smart services and so on. The basic and important requirement of the above services and technologies are storage and computation. The cloud computing called centralized server plays a major role for storage and computation in all over the world. Because of the development of technologies, the centralized database is facing difficulties to manage the needs of these types of upgrading technologies. To enhance and fulfil the service gap faced by the cloud, many network computers models or stake cloud computing are raised such as grid computing, edge computing, utility computing, green computing, fog computing and dew computing have been created and developed by the scholastic and assiduity group. With that they develop many various types of usage to enhance the basic concept of cloud computing. The main target is to take a cloud computing approach to reach the end user such as a local or edge server to overcome the difficulties faced by the cloud computing and give the best performance to the end user or customer experience. In this survey paper, we theoretically and technologically analyzed the stake cloud computing including grid computing, fog computing, dew computing, edge computing, utility computing and green computing via several aspects and examples with cloud computing. Finally, we concluded this paper with the stake cloud computing development promise to help the society in various fields from various authors perspective.